The Role of Accountants in Optimizing Regional Original Revenue (ROR) with Proper Central and Regional Financial Management - Dito Aditia Darma Nst; Renny Maisyarah; Linda Asriani; Evan Tamaro; Dedi Agus Pratikno; Ashri.A.Handayani; Jefri Ronaldo (International Journal of Management, Economic and Accounting, 2024)
Regional Original Revenue (ROR) is the main source of financing for local governments in carrying out various development programs. Despite its importance, many districts/cities in Indonesia still face challenges in optimizing ROR. In this context, accountants play a crucial role, not only in the preparation of financial statements, but also in analysis, auditing, and budget planning. This journal aims to explore the role of accountants in improving ROR, identify strategies that can be implemented, and discuss the challenges faced. Through literature analysis and case studies, it was found that increasing the capacity of human resources, optimizing tax management, and utilizing information technology are important steps that can be taken. This study aims to find out and analyze the role of accountants and how they can contribute to overcoming existing challenges, as well as improving the effectiveness of regional financial management in Indonesia. The research method applied is qualitative descriptive with documentation studies, where data collection techniques use documentation studies. The results of this study are expected to provide useful recommendations for local governments in an effort to increase revenue and financial accountability in response to government demands on reform in the field of central and regional financial relations in accordance with Law No. 22/1999. Regional financial reform has given birth to Government Regulation (PP) No. 105 of 2000 concerning Regional Financial Management and Accountability. One of the problems that arises from the PP is about the reporting and financial accountability management system. This problem can be overcome by implementing ASP and training human resources of central and regional governments in the field of ASP, so that it can create good governance. This is the role of universities as centers for education, training and financial research, especially in the development of the field of Public Sector Accounting to prepare human resources for the financial management system